2012
DOI: 10.1007/s10965-011-9811-3
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization kinetics of 2-phenylethyl (meth)acrylates studied by photo DSC

Abstract: The present work deals with the photopolymerization of 2-phenylethyl (meth)acrylates and estimation of their kinetic parameters. Formulations were made by independently homogenizing the monomers with photoinitiators of two different classes. Two different compositions of photoinitiators were used to study the effect of concentration of photoinitiator on cure kinetics. These compositions obtained were tested for photo curing performance using differential photocalorimetry (DPC) or photo DSC under polychromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…However, the resins with slower reacting methacrylate RDs, AESO/IBOMA and AESO/THFMA, showed the higher G ′ values at the end of the process and thus more rigid polymers were formed in these cases. This observation correlates with previously determined the higher conversion of methacrylate groups in comparison to acrylate groups resulting in polymers with better mechanical properties 48 . Moreover, it was observed that the rate of cross‐linking was associated with the material shrinkage during the photopolymerization 49,50 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the resins with slower reacting methacrylate RDs, AESO/IBOMA and AESO/THFMA, showed the higher G ′ values at the end of the process and thus more rigid polymers were formed in these cases. This observation correlates with previously determined the higher conversion of methacrylate groups in comparison to acrylate groups resulting in polymers with better mechanical properties 48 . Moreover, it was observed that the rate of cross‐linking was associated with the material shrinkage during the photopolymerization 49,50 .…”
Section: Resultssupporting
confidence: 90%
“…This observation correlates with previously determined the higher conversion of methacrylate groups in comparison to acrylate groups resulting in polymers with better mechanical properties. 48 Moreover, it was observed that the rate of cross-linking was associated with the material shrinkage during the photopolymerization. 49,50 The shrinkage is caused by the transformation of intermolecular distances $3-5 Å linked via weak Van der Waals force into the typical C C strong covalent bond distance $1.54 Å.…”
Section: Kinetics Of Photocross-linkingmentioning
confidence: 99%
“…The low final conversion of the methacrylates compared to the acrylates is not necessarily surprising. Other researchers have observed the slow reaction rates of methacrylates compared to acrylates during photopolymerization reactions . The slow R p values of methacrylates have been attributed to the stability of the tertiary propagating methacrylate radical (in comparison to the secondary propagating acrylate radical), as well as the increased steric hindrance caused by the additional C─H bonds .…”
Section: Resultsmentioning
confidence: 99%
“…This parameter can be obtained using the Jacob's equation based on the Beer‐Lambert law shown in Equation (1) [ 58,59 ] Cdbadbreak=DplnE0Enormalc\begin{equation}{C_{\rm{d}}}\; = \;{D_{\rm{p}}}\;{\rm{ln}}\frac{{{E_0}}}{{{E_{\rm{c}}}}}\end{equation}…”
Section: Methodsmentioning
confidence: 99%